2019
DOI: 10.1098/rspb.2019.1177
|View full text |Cite
|
Sign up to set email alerts
|

The biggest losers: habitat isolation deconstructs complex food webs from top to bottom

Abstract: Habitat fragmentation threatens global biodiversity. To date, there is only limited understanding of how the different aspects of habitat fragmentation (habitat loss, number of fragments and isolation) affect species diversity within complex ecological networks such as food webs. Here, we present a dynamic and spatially explicit food web model which integrates complex food web dynamics at the local scale and species-specific dispersal dynamics at the landscape scale, allowing us to study the interplay of local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 57 publications
12
54
0
Order By: Relevance
“…In the literature, an increased risk of extinction has been related to various indicators such as high trophic level, large body size, and low abundance (Gaston and Blackburn, 1995;Purvis et al, 2000;Cardillo et al, 2005;Davidson et al, 2009;Lee and Jetz, 2011). In agreement with several previous studies (Kondoh, 2003;van Nouhuys, 2005;Eklöf and Ebenman, 2006;Curtsdotter et al, 2011;Liao et al, 2017b;Ryser et al, 2019), we found that species at higher trophic levels indeed tend to suffer elevated extinction risks. Differences in other indicators can be accounted for through their effects on the species-level parameters π k i and ξ i .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the literature, an increased risk of extinction has been related to various indicators such as high trophic level, large body size, and low abundance (Gaston and Blackburn, 1995;Purvis et al, 2000;Cardillo et al, 2005;Davidson et al, 2009;Lee and Jetz, 2011). In agreement with several previous studies (Kondoh, 2003;van Nouhuys, 2005;Eklöf and Ebenman, 2006;Curtsdotter et al, 2011;Liao et al, 2017b;Ryser et al, 2019), we found that species at higher trophic levels indeed tend to suffer elevated extinction risks. Differences in other indicators can be accounted for through their effects on the species-level parameters π k i and ξ i .…”
Section: Discussionsupporting
confidence: 90%
“…Here we have studied the effect of habitat loss on food webs by developing a novel approach to trophic metacommunities, combining the methods of classic metapopulation models on fragmented landscapes (Hanski andOvaskainen, 2000, 2003;Ovaskainen and Hanski, 2001;Grilli et al, 2015) with a Bayesian network representation of trophic interactions (Eklöf et al, 2013) for calculating local extinction rates. The approach has much of the flexibility of explicit dynamical models (Ryser et al, 2019), but is close in tractability and computational efficiency to simple topological methods (Dunne and Williams, 2009). This allows one to apply it to much larger food webs and landscapes than would be feasible with fully fledged dynamical models, while still retaining the ability to make predator extinction a smooth function of prey absence (as in Cazelles et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to the prediction of Rip and McCann (2011), low dispersal mortality does not generally result in higher α - or even γ -variability in our model. We attribute this counter-intuitive trend to an indirect effect of dispersal mortality: Despite their superior dispersal abilities, top predators often suffer most from landscape fragmentation because they are energetically more limited than the species on lower trophic levels (Ryser et al, 2019). In fact, we also find that the lower the landscape connectance, the lower the mean biomass of the predator (see Online Resource, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Animals rarely move unrestrictedly, as the physical habitat environments they depend on are often heterogeneous and uneven (Fahrig, 2007;Lovett et al, 2007;Kovalenko et al, 2012). By shaping individual movements, the physical configuration of habitats can have implications for population and community dynamics, including ecological interactions (Plitzko and Drossel, 2015;Jordano, 2016;Ryser et al, 2019), community structure (Altermatt and Holyoak, 2012;Henriques-Silva et al, 2013;Wilson et al, 2016), and speciation (Naka and Brumfield, 2018). Habitat configuration can also determine the rates of social interactions among conspecifics, thus shaping the social structure of populations (Emlen and Oring 1977;Gosling 1991;Leu et al, 2016;Farine and Sheldon, 2019;.…”
Section: Introductionmentioning
confidence: 99%